Gillespiе syndrome, caused by previously undescribed mutation in the gene ITPR1 - I. V. Sharkova; I. A. Akimova; O. V. Khlebnikova; E. L. Dadali (Русский журнал детской неврологии)
Gillespie syndrome is one of the rare monogenic syndromes characterized by a combination of congenital muscular hypotonia, delayed psychomotor and speech development, ataxia and hypoplasia of the iris. The cause of disease – homozygous, compound heterozygous and heterozygous mutations in the gene ITPR1.We described a case history of a child of 1 year and 8 months whose parents were complaining of severe delay in psychomotor and speech development, and a violation of the functions of the visual analyzer. Neurological and ophthalmologic examinations were performed according to a standard procedure. Search for mutations was carried out using high-performance exome sequencing on NextSeg 500 (Illumina, USA) with an average coverage of at least 70–100x.Clinical and genetic characteristics of the patient with Gillespie syndrome due to the newly identified heterozygous missense mutation are presented. Mutation 1865T˃S in the 18 exon of the ITPR1 gene was found during the new generation sequencing of the exome. In the future, these data can be used to predict the characteristics of clinical manifestations and the severity of Gillespie syndrome, when a similar nucleotide substitution will be found in other patients.